Clinical profile and outcomes of patients with acute pancreatitis and correlation with severity index from a tertiary care centre in South India-retrospective analysis - Nawahir, Sultan; S., Babu Kumar; Naik, Bala Kasi; Parthasarathy, Ealai Athmarao (International Journal of Advances in Medicine, 2021)
Background: Acute pancreatitis is an inflammatory condition of the pancreas having a varied clinical presentation. It is one of the commonest causes of abdominal pain requiring hospital admission. This retrospective study aims to describe the clinical profile and outcomes of patients with acute pancreatitis and its correlation with severity index. Methods: All patients admitted with a diagnosis of acute pancreatitis to medical gastroenterology department between January 2018 to December 2020 were included in this retrospective study. Results: A total of 61 subjects were included in the final analysis. The mean age was 41.64, the ranged between 19 to 88 years. Among the study population, 53 (86.89%) were male and 8 (13.11%) were female. Among the people 43 (70.49%) were alcoholics, 22 (36.07%) were smokers, 11(18.03%) had systemic hypertension and 5 (8.20%) participants had type 2 diabetic mellitus. The mean CTSI was 2.15±2.82, the mean Balthazar was 3.43±2.4 and the mean procalcitonin was 2.52±9.28. The mean Lipase was 7822. There was a weak positive correlation between CTSI and CRP (rs value: 0.147, p=0.260). There was a weak negative correlation between Balthazar and CRP (rs value:-0.067, p=0.606). Conclusions: Among the study population, 87% of the patients were males. 70% of the population were alcoholics. Mean serum lipase was 7822. There was a weak positive correlation between CTSI and CRP (rs value: 0.147, p=0.260). There was a weak negative correlation between Balthazar and CRP (rs value:-0.067, p=0.606).